WORKING MEMORY CAPACITY TEST REVEALS SUBJECTS DIFFICULTIES MANAGING LIMITED CAPACITY - R V Ershova; Tarnow Eugen (Peoples' Friendship University of Russia (RUDN University), 2016)
Free recall consists of two separate stages: the emptying of working memory and reactivation [5]. The Tarnow Unchunkable Test (TUT, [7]) uses double integer items to separate out only the first stage by making it difficult to reactivate items due to the lack of intra-item relationships.193 Russian college students were tested via the internet version of the TUT. The average number of items remembered in the 3 item test was 2.54 items. In the 4 item test, the average number of items decreased to 2.38. This, and a number of other qualitative distribution differences between the 3 and 4 item tests, indicate that the average capacity limit of working memory has been reached at 3 items. This provides the first direct measurement of the unchunkable capacity limit of number items.Difficulties in managing working memory occurred as most subjects remembered less as the number of items increased beyond capacity and failed to remember a single item in at least one out of three 4 item trials. The Pearson correlation between the total recall of 3 and 4 items was a small 38%.